DNA Repair Mechanisms in Multi Drug Resistant Bacteria: Impact on Genome Stability and Antibiotic Resistance - Shakeel, Faiqa; Mustafa, Iman; Shahid, Ruba; Noor, Amna; Fatima, Mishaal; Ghafoor, Kiran; AminaTariq; Zulfiqar, Samra (Indus Journal of Bioscience Research, 2025)
Conventional antibiotics are becoming less effective as the global health crisis of multidrug-resistant (MDR) bacterial infections worsens. The function of bacterial DNA repair systems in promoting MDR is a quickly developing paradigm, despite the well-established nature of conventional resistance mechanisms such as efflux pumps and drug-inactivating enzymes. The present understanding of how DNA repair pathways, which are necessary for the stability of the genome, paradoxically promote adaptive mutagenesis and horizontal gene transfer under antibiotic stress is summarized in this review. In important MDR pathogens, we investigate the complex interactions among repair mechanisms, stress reactions, and resistance evolution. The regulatory crosstalk with other bacterial systems and the potential of DNA repair inhibitors as novel therapeutic adjuvants are two examples of significant knowledge gaps that are highlighted. We wrap up by going over potential future directions for focusing on DNA repair to re-sensitize MDR bacteria and prolong the effectiveness of current antibiotics.